QUANTUM CHEMICAL STUDY ON THE SOLVATION OF LITHIUM CHLORIDE IN DIMETHYL AND DIETHYL SULFONES (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
LiCl–dimethyl sulfone and LiCl–diethyl sulfone systems have been investigated by restricted Hartree-Fock (RHF/6-311++G(d, p)) computations in order to establish the structural and spectral parameters of solute–solvent systems. The calculations show the existence of two stable LiCl–sulfone (1:1) structures and one transition state. It was shown that sensitivity of the CH and SO stretching vibrations to the interaction between LiCl and sulfone strongly depends on the structure of the complex, and the difference in their properties is explained in the frame of vibrational Stark effect, rather than by specific solute-solvent interactions only. Results are compared to the solid state experimental spectra.
Keywords: sulfone, lithium chloride, ab initio calculations, IR spectra, Stark effect